If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + 5) + x + -10 = 84 Reorder the terms: 10(5 + x) + x + -10 = 84 (5 * 10 + x * 10) + x + -10 = 84 (50 + 10x) + x + -10 = 84 Reorder the terms: 50 + -10 + 10x + x = 84 Combine like terms: 50 + -10 = 40 40 + 10x + x = 84 Combine like terms: 10x + x = 11x 40 + 11x = 84 Solving 40 + 11x = 84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 11x = 84 + -40 Combine like terms: 40 + -40 = 0 0 + 11x = 84 + -40 11x = 84 + -40 Combine like terms: 84 + -40 = 44 11x = 44 Divide each side by '11'. x = 4 Simplifying x = 4
| 2-7(4a+1)=-89 | | 13t-15t=12 | | 2x+2=20-4x | | 6x-14=15+5x | | -5n-11=29 | | 17.5+(-42.2)= | | (3x-17)(9x^2-42x+49)=0 | | 5x-23=10x-47 | | 1+4n=-13+5n-8n | | 8x=12+x^2 | | 5x+(x-2)+3(x-4)=1 | | 17.5-(42.2)= | | -m^2+14-16m^2+13+m^2= | | (4x-5)(6x+5)= | | 108=-5x+3 | | x-2(x+3)+4(x-1)=2 | | x-2(x+3)+4(x-1)=22 | | -5(3x-5)=-15x+25 | | 2x(x+3y+4z)= | | 11*1.86-12= | | X^2+1x+.25=0 | | -31-9x=-6x+32 | | y-x^2+6x=k | | 5x-10+(-9)=-7+7x | | 8x+11=3x-19 | | -14b-5=12b+8 | | -20-6x=6-4x | | 4x+4(x-1)+2(x-3)=0 | | 21=-27+6x | | -3(9+a)=33 | | 8+11a=-234 | | B(3b-1)= |